Na fali transhumanizmu - MUZYKA, Kamil (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2015)
Recenzja książki: The Transhumanist Reader: Classical and Contemporary Essays on the Science, Technology, and Philosophy of the Human Future, red. M. More, N. Vita-More, John Wiley & Sons, Inc., Malden–Oxford–Chichester 2013.